PENGELOLAAN DANA BANTUAN OPERASIONAL SEKOLAH (BOS) SEKOLAH DASAR NEGERI KECAMATAN MANDIANGIN KOTO SELAYAN KOTA BUKITTINGGI - Afrilliana Fitri (Universitas Negeri Padang, 2014)
The purpose of this research is to know the Management Fund BOS. This research is a research popolasi in which the entire population as a sample of 51 people, consisting of the principal, the Treasurer, and the school Committee. This research Instrument using a Likert scale has tested the validity and reliabelitasnya. Data analysis using the formula of Mean. The results of this research fund manager is the BOSS simply carry out the management. Key word: the Management Fund BOS.